2020
DOI: 10.1093/cid/ciaa1790
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Case of Homozygous Interferon Alpha/Beta Receptor Alpha Chain (IFNAR1) Deficiency With Hemophagocytic Lymphohistiocytosis

Abstract: We present a case of complete deficiency of the Interferon alpha/beta receptor alpha chain (IFNAR1) in a child with fatal systemic hyperinflammation, apparently provoked by live-attenuated viral vaccination. Such pathologic hyperinflammation, fulfilling criteria for haemophagocytic lymphohistiocytosis, is an emerging phenotype accompanying inborn errors of type I interferon immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…No nonsynonymous variants of IFNAR1 , IFNAR2 , or the five genes controlling the type I IFN response pathway ( JAK1 , TYK2 , STAT1 , STAT2 , and IRF9 ; Bastard et al, 2020a ; Dupuis et al, 2003 ; Eletto et al, 2016 ; Gothe et al, 2020 ; Hambleton et al, 2013 ; Hernandez et al, 2018 ; Kreins et al, 2015 ; Watford and O’Shea, 2006 ) were found in the other six patients. We then hypothesized that these patients might have an autoimmune phenocopy of inborn errors of type I IFN immunity, as recently shown in patients with life-threatening COVID-19 pneumonia ( Bastard et al, 2020b ; Ku et al, 2020 ; Zhang et al, 2020a ; Zhang et al, 2020b ).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…No nonsynonymous variants of IFNAR1 , IFNAR2 , or the five genes controlling the type I IFN response pathway ( JAK1 , TYK2 , STAT1 , STAT2 , and IRF9 ; Bastard et al, 2020a ; Dupuis et al, 2003 ; Eletto et al, 2016 ; Gothe et al, 2020 ; Hambleton et al, 2013 ; Hernandez et al, 2018 ; Kreins et al, 2015 ; Watford and O’Shea, 2006 ) were found in the other six patients. We then hypothesized that these patients might have an autoimmune phenocopy of inborn errors of type I IFN immunity, as recently shown in patients with life-threatening COVID-19 pneumonia ( Bastard et al, 2020b ; Ku et al, 2020 ; Zhang et al, 2020a ; Zhang et al, 2020b ).…”
Section: Resultsmentioning
confidence: 89%
“…Auto-Abs against type I IFNs can therefore underlie severe COVID-19 or YFV-17D disease. Intriguingly, children with APS-1 and auto-Abs to type I IFNs have been vaccinated with MMR without any reported adverse reaction, despite the occurrence of MMR disease in several patients with inherited IFNAR1 or IFNAR2 deficiency ( Bastard et al, 2020a ; Duncan et al, 2015 ; Gothe et al, 2020 ; Hernandez et al, 2019 ). This may be due to the activity of IFN-β, IFN-κ, or IFN-ε in APS-1 patients, whose auto-Abs typically neutralize the 13 individual IFN-α2 and IFN-ω ( Bastard et al, 2020b ; Meager et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only nine patients with autosomal recessive (AR) complete IFNAR1 deficiency from six unrelated kindreds have been described to date [45,[87][88][89] (Table 2). Most of the causal mutations are nonsense mutations or substitutions of essential splice sites, resulting in a premature stop codon and an absence of functional IFNAR1.…”
Section: Human Ar Ifnar1 Deficiencymentioning
confidence: 99%
“…The MIS-C observed in this child is a novel phenotype associated with IFNAR1 deficiency. Intriguingly, progressive hemophagocytosis after MMR vaccine or cytomegalovirus infections was noted in two of the previously reported cases [ 43 , 44 ], as well as in patients with other defects in the type I IFN pathway including STAT1 [ 49 ], STAT2 [ 50 , 51 ], and IFNAR2 [ 9 , 52 ]. Despite exaggerated inflammation, our patient did not fulfill the diagnostic score of hemophagocytosis (Hscore [ 53 ]: 106).…”
Section: Discussionmentioning
confidence: 99%